Idealized Body Images and Fitness Lifestyles on Social Media: A Systematic Review Exploring the Link Between Social Media Use and Symptoms of Orthorexia Nervosa and Muscle Dysmorphia - Vintró‐Alcaraz, Cristina; Ballero Reque, Cristina; Paslakis, Georgios; Testa, Giulia (European eating disorders review, 2025)
Frequent social media use is associated with orthorexia and muscle dysmorphia symptoms. Fitspiration and thinspiration content strongly link to orthorexia symptoms. Social media addiction shows ties to orthorexia and muscle dysmorphia symptoms.